Think Python How to Think Like a Computer Scientist - Downey, Allen B.; Open Textbook Library (Open Textbook Library, 2012)
Think Python is a concise introduction to software design using the Python programming language. Intended for people with no programming experience, this book starts with the most basic concepts and gradually adds new material. Some of the ideas students find most challenging, like recursion and object-oriented programming, are divided into a sequence of smaller steps and introduced over the course of several chapters. This textbook has been used in classes atBard College,Olin College of Engineering, University of California, Santa Barbara, University of Maine, University of Northern Colorado.
1 The way of the program -- 2 Variables, expressions and statements -- 3 Functions -- 4 Case study: interface design -- 5 Conditionals and recursion -- 6 Fruitful functions -- 7 Iteration -- 8 Strings -- 9 Case study: word play -- 10 Lists -- 11 Dictionaries -- 12 Tuples -- 13 Case study: data structure selection -- 14 Files -- 15 Classes and objects -- 16 Classes and functions -- 17 Classes and methods -- 18 Inheritance -- 19 Case study: Tkinter -- A Debugging -- B Analysis of Algorithms -- C Lumpy
In English.
Description based on print resource
Keywords: Computer Science -- Textbooks; Programming Languages -- Textbooks